Platelet-Rich Plasma in Androgenic Alopecia: Myth or an Effective Tool - Khatu, Swapna S (Medknow Publications & Media Pvt Ltd, 2014)
Platelet-rich plasma (PRP) has become a newer method for the treatment of various types of alopecia. In this prospective study, safety, efficacy and feasibility of PRP injections in treating androgenic alopecia were assessed. Eleven patients suffering from hair loss due to androgenic alopecia and not responding to 6 months treatment with minoxidil and finasteride were included in this study. The hair pull test was performed before every treatment session. A total volume of 2-3 cc PRP was injected in the scalp by using an insulin syringe. The treatment was repeated every two weeks, for a total of four times. The outcome was assessed after 3 months by clinical examination, macroscopic photos, hair pull test and patient's overall satisfaction. RESULTS: A significant reduction in hair loss was observed between first and fourth injection. Hair count increased from average number of 71 hair follicular units to 93 hair follicular units. Therefore, average mean gain is 22.09 follicular units per cm(2.) After the fourth session, the pull test was negative in 9 patients. CONCLUSION: PRP injection is a simple, cost effective and feasible treatment option for androgenic alopecia, with high overall patient satisfaction.